Accumbal and pallidal dopamine, glutamate and GABA overflow during cocaine self‐administration and its extinction in rats. (14th January 2013) - Wydra, Karolina; Golembiowska, Krystyna; Zaniewska, Magdalena; Kamińska, Katarzyna; Ferraro, Luca; Fuxe, Kjell; Filip, Małgorzata
Abstract We investigated the changes in dopamine (DA), glutamate and γ‐aminobutyric acid (GABA) during cocaine self‐administration in rats implanted with guide cannulae into the nucleus accumbens and ventral pallidum. After stabilized cocaine self‐administration, separate groups of rats underwent extinction (10 days) procedure in which cocaine infusion was replaced by saline injections. With using a 'yoked' procedure, the effects of cocaine or its withdrawal on the level of neurotransmitters were evaluated by dual‐probe microdialysis. Repeated cocaine administration reduced basal glutamate levels in the nucleus accumbens and ventral pallidum, whereas it did not affect basal accumbal DA levels. Only rats that self‐administered cocaine had increased basal GABA overflow in both examined brain structures. Active or passive cocaine administration elevated extracellular accumbal DA, however, the extent of cocaine‐evoked DA level was significantly higher in rats that self‐administered cocaine while both groups of animals showed also an attenuation of GABA level in the nucleus accumbens. On day 10 of extinction training, rats previously given cocaine revealed decreases in the basal accumbal concentration of glutamate while the basal GABA levels were significantly enhanced as compared with baseline of saline‐yoked controls. Potassium depolarization delayed the reduction of the accumbal and pallidal extracellular glutamate levels in the active and passive cocaine groups. The present data indicate that changes in DA and GABA neurotransmission during maintenance phase mirror the motivational aspects of cocaine intake. Depending on acute (24 hours) or late (10 days) cocaine withdrawal, different neurotransmitter systems (i.e. glutamate or GABA) seem to be involved.